1993
DOI: 10.3109/03093649309164350
|View full text |Cite
|
Sign up to set email alerts
|

Dundee revisited — 25 years of a total amputee service

Abstract: The Dundee Limb Fitting Centre has provided an integrated rehabilitation programme for the amputee since 1965.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 7 publications
1
16
0
1
Order By: Relevance
“…atherosclerosis and diabetes) are the most frequent cause for amputation. 8,9 The survival rate of vascular TFA in the Netherlands is 50% after 1.2 years. 10 This explains the apparent overrepresentation of young patients in the present study with a traumatic amputation.…”
Section: Discussionmentioning
confidence: 99%
“…atherosclerosis and diabetes) are the most frequent cause for amputation. 8,9 The survival rate of vascular TFA in the Netherlands is 50% after 1.2 years. 10 This explains the apparent overrepresentation of young patients in the present study with a traumatic amputation.…”
Section: Discussionmentioning
confidence: 99%
“…For a patient with a recent amputation, our data showed that 3 months or 1 year is a large percentage of the patient's remaining life span and that rehabilitation must focus on appropriate activities that help patients function more quickly, thus adding quality to their remaining lifetime. While mortality following a lower-limb amputation for vascular disease is high, many patients who survive the immediate postoperative period receive a prosthesis [1,7,9,[34][35][36][37][38]. These patients function reasonably well, at least in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary source was an independent computerized database of all patients attending the Dundee Limb Fitting Centre, which provides a rehabilitation service for the whole of Tayside (13). Two possible sources of subjects were used to maximize ascertainment.…”
Section: Case Definitionmentioning
confidence: 99%